BEHAVIORAL FACTORS INFLUENCING COUNTRIES’ BUSINESS PRACTICES: THE ROLE OF DIGITAL TRANSFORMATION - Yuesti, Anik; Madrigal, Dennis V.; Osano, Hazel S. (EMAS, 2025)
In the era of globalization and technology-driven business environment, it is becoming more and more important to have a better understanding about how behavioral factors are perceived in the context of countries’ business practices. This research examines the impact of behavioral factors on business practices across nations, highlighting the role of digital transformation as a mediating factor. Based on a quantitative approach, the research was developed among international business practitioners and analyzed using SPSS. Findings show national business practices are significantly impacted by both cultural values and communication styles. Moreover, digital transformation was found to mediate these relationships, helping to optimize the way behavioral factors are translated into successful business strategies. Results reveal the applicability of Hofstede’s cultural dimensions theory and point out that digital readiness enhances organizational adaptability and cross-cultural management and performance. By exploring the intersection of behavior and technology, the study provides practical insights for global managers and policy makers aiming to align cultural awareness with digital advancement in shaping sustainable international business practices.